2020
DOI: 10.1111/jcpe.13378
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as a risk factor for tooth loss over 5 years: A population‐based cohort study

Abstract: Tooth loss has a negative impact on individuals' life and well-being (Emami et al. 2013). Globally, total tooth loss is estimated to affect 267 million individuals and account for 7.3 million years lived with disability (Collaborators et al. 2020). Although estimates of severe tooth loss generally have decreased (Kassebaum et al. 2014), population-based studies still demonstrate high number of lost teeth over time in various countries (Dye et al. 2019; Muller et al. 2007). Caries and periodontitis are recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
(57 reference statements)
1
6
1
Order By: Relevance
“…Moreover, chronic systemic inflammation impairs the individual's immune response and, therefore, increases the risk of periodontitis onset and progression, 8,29 which may result in tooth loss. 6 On a similar note, the findings of our study agree with the previous literature, showing that obesity, [30][31][32] dysglycemia, 33 reduced HDL cholesterol 34 and hypertension 35 are also associated with tooth loss through the same aforementioned mechanisms. Then, the combination of these metabolic abnormalities in MetS can reinforce its effect on tooth loss.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, chronic systemic inflammation impairs the individual's immune response and, therefore, increases the risk of periodontitis onset and progression, 8,29 which may result in tooth loss. 6 On a similar note, the findings of our study agree with the previous literature, showing that obesity, [30][31][32] dysglycemia, 33 reduced HDL cholesterol 34 and hypertension 35 are also associated with tooth loss through the same aforementioned mechanisms. Then, the combination of these metabolic abnormalities in MetS can reinforce its effect on tooth loss.…”
Section: Discussionsupporting
confidence: 92%
“…Our data confirm evidence found in previous studies indicating that obese subjects present more severe cases of periodontitis than normo-weighted subjects, independently of their oral hygiene habits [ 17 ]. A recent study showed that obesity is also associated with a higher risk of tooth loss over five years [ 34 ]. In our study, obese subjects had significantly more missing teeth than normo-weighted subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Several cohort and intervention studies related to obesity and periodontitis have been conducted. Recent cohort studies indicated that obesity is a risk factor for tooth loss [71] and that obesity is associated with worse mean probing pocket depth following periodontal therapy [72•]. Several reports have investigated the association between the degree of obesity and systemic effects of periodontal inflammation.…”
Section: Clinical Studies On the Association Of Periodontitis And Obesitymentioning
confidence: 99%